Misurare la vitalità delle piante per mezzo della fluorescenza della clorofilla - Desotgiu, Rosanna (Strumenti per la didattica e la ricerca, 2012)
The book begins with a detailed description of the characteristics of the photosynthetic apparatus and the processes that take place there, to then present the general principles of fluorescence. After that, it gives a description of the characteristics of direct and modulated fluorescence and a presentation of the shared and distinctive parameters of these two techniques. Then a brief presentation is made of other innovative approaches to the analysis of fluorescence (Chlorophyll Fluorescence Imaging - CFI, P700 absorbance, delayed fluorescence) and the relative tools. An important part of the book comprises a description of the possible applications of fluorescence techniques for the analysis of various types of stress (aridity, strong light radiations, UV, high and low temperatures, salinity, weedkillers, pollution, etc.) and, consequently, their possible use in agriculture, forestry and to protect the environment.